Co-administration of dexamethasone with peripheral nerve block: intravenous vs perineural application: systematic review, meta-analysis, meta-regression and trial-sequential analysis. (February 2018) - Heesen, M.; Klimek, M.; Imberger, G.; Hoeks, S.E.; Rossaint, R.; Straube, S.
Abstract: Background: I.V. and perineural dexamethasone have both been found to prolong loco-regional analgesia compared with controls without dexamethasone. It is unclear whether perineural administration offers advantages when compared with i.v. dexamethasone. Methods: A systematic literature search was performed to identify randomized controlled double-blind trials that compared i.v. with perineural dexamethasone in patients undergoing surgery. Using the random effects model, risk ratio (for binary variables), weighted mean difference (for continuous variables) and 95% confidence intervals were calculated. We applied trial sequential analysis to assess the risks of type I and II error, meta-regression for the study of the doseresponsive relationship, and the Grading of Recommendations Assessment, Development, and Evaluation system. Results: We identified 10 randomized controlled double-blind trials (783 patients). When using conventional meta-analysis of nine low risk of bias trials, we found a statistically significantly longer duration of analgesia, our primary outcome with perineural dexamethasone (241 min, 95%CI, 87, 394 min). When trial sequential analysis was applied, this result was confirmed. Meta-regression did not show a dose-response relationship. Despite the precision in the results, using the Grading of Recommendations Assessment, Development, and Evaluation system (GRADE), we assessed the quality of the evidence for our primary outcome as low. Conclusions: There is evidence that perineural dexamethasone prolongs the duration of analgesia compared with i.v. dexamethasone. Using GRADE, this evidence is low quality.